Hubungan Karakteristik dan Respons Petani Terhadap Program Kartu Tani di Kecamatan Tasikmadu, Kabupaten Karanganyar - Fahbri Yola Oktaviani; Sapja Anantanyu; Eksa Rusdiyana (Universitas Sebelas Maret, 2024)
The farmer card program was launched in 2016 with the initial aim of streamlining the distribution of subsidized fertilizers, and only small farmers are targeted by this program. One of the sub-districts in Karanganyar Regency that has implemented the farmer card program is Tasikmadu. Almost all farmers registered in e-RDKK/e-Alokasi already have a farmer card, and Tasikmadu became the sub-district with the highest purchase of subsidized fertilizer using the farmer card in Karanganyar in 2020. This farmer card program raises various responses from various characteristics of farmers. This research aims to explore the correlation between characteristics and responses of farmer to the farmer card program in Tasikmadu Sub-district, Karanganyar Regency. The primary research method is quantitative, and location determination is intentionally (purposely) in Tasikmadu Sub-district, Karanganyar Regency. Sampling was carried out using the multi-stage cluster random sampling method, with a total of 60 farmers as samples. The data used consists of primary and secondary data. Primary data was obtained through interviews using questionnaires, while secondary data were obtained from related parties in this study, namely the Tasikmadu Sub-district office, Agricultural Extension Center (BPP) Tasikmadu, and previous research. The data analysis was carried out using Rank Spearman analysis. The results show that there is a significant relationship between age, education level, extension activities, and access to information with farmers’ responses to the farmer card program. However, there is no significant relationship between farming experience and land size with the farmer card program.